Expo Gallery Batik Bakaran in Pati Regency with Neo Vernacular Architecture Approach - Ikelana Mukti; Diharto; Teguh Prihanto; Isna Pratiwi (Canopy: Journal of Architecture, 2024)
Bakaran Batik is a cultural heritage originating from Pati Regency. Burnt Batik has now been designated as one of the Intangible Cultural Heritage (WBTb) on a national scale. However, as time goes by, its existence among the community is starting to decline in Bakaran Batik. The planning of the Bakaran Batik Expo Gallery in Pati Regency is aimed at preserving the art of batik itself and presenting Bakaran Batik as batik which has its own characteristics, both in terms of motifs, patterns and colors, to the public. wide. The site used in planning the Bakaran Batik Expo Gallery in Pati Regency is located on Jalan Raya Sunan-Ngerang, Bakaran Kulon Village, Juwana District, Pati Regency, 59185. The Expo Gallery Batik Bakaran building applies the Neo-Vernacular architectural concept which adopts the form of a Joglo Traditional House. The environmental aspects used in designing the Bakaran Batik Expo Gallery include rain water harvesting, and the processing of batik waste that does not pollute the surrounding environment. From several planning and design approaches, a planning and design concept was obtained which was used as the basis for planning the design of the Bakaran Batik Expo Gallery in Pati Regency. Some of these approaches include the functional approach, structural approach, performance aspects approach, and architectural approach.